Copper-based composite solder paste, preparation method and application thereof

By using mixed grinding technology of doped modified diamond powder and titanium powder in copper-based composite solder paste, the problem of poor fusion of diamond and copper interface is solved, and the thermal conductivity and high temperature stability of semiconductor devices are significantly improved.

CN119216870BActive Publication Date: 2025-02-18CAI LUN ADVANCED SEMICONDUCTOR MATERIALS (CHONGQING) CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411731757.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-02-18
Estimated Expiration
2044-11-29

AI Technical Summary

Technical Problem

In the prior art, diamond and copper have poor fusion properties and are not tightly bonded to each other, resulting in poor thermal conductivity and high temperature stability of semiconductor devices made of copper-based composite materials.

Method used

Copper-based composite solder paste is used, which includes nano-scale copper powder, micro-scale doped modified diamond powder, titanium powder, additives, solvents and resins. By mixing and grinding of doped modified diamond powder and titanium powder, the bonding force between diamond and titanium powder is increased, and a tighter interface bond is formed during the sintering process.

Benefits of technology

The thermal conductivity and high temperature stability of semiconductor devices are significantly improved, while reducing the overall thermal expansion coefficient of the solder layer and reducing the thermal stress between the chip and the solder layer during temperature changes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119216870B_ABST
    Figure CN119216870B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of semiconductor technology, and specifically relates to a copper-based composite solder paste, a preparation method and application thereof. The copper-based composite solder paste comprises: nano-scale copper powder, micron-scale doped modified diamond powder, titanium powder, additives, solvents and resins. The copper-based composite solder paste of the present invention, by adding micron-scale doped modified diamond powder (i.e., doping and modifying micron diamond), can allow doping atoms such as boron, sulfur, nitrogen, phosphorus and magnesium to penetrate into the micron diamond lattice, which helps to improve the electrical conductivity, and the improvement of the electrical conductivity helps to reduce the heat generation power of the solder layer, thereby improving the thermal conductivity and high-temperature stability of the semiconductor device.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of semiconductors, and in particular relates to a copper-based composite solder paste, a preparation method and application thereof. Background Art

[0002] With the continuous advancement of microelectronics technology, the performance and integration of electronic devices have been rapidly improved, which has put forward higher requirements for microelectronics packaging technology, especially in terms of heat dissipation and conductivity. Traditional packaging materials can no longer meet the needs of high-end microelectronic devices. Therefore, it is particularly important to research and develop new high-performance microelectronic packaging materials.

[0003] Copper-based composite materials refer to new materials prepared by appropriate methods with copper as the matrix and reinforcement phases such as particles, whiskers, and fibers. Copper-based composite materials have both good electrical and thermal conductivity of copper alloys and good strength, are easy to process, and are corrosion-resistant. They are widely used in electrical contact materials, electronic packaging materials, heat exchange materials, and other fields. However, it is difficult to take into account the strength, electrical conductivity, and thermal conductivity of copper-based composite materials at the same time.

[0004] To further improve the performance of copper-based composites, people have tried to add diamond particles to the copper matrix. Diamond is known for its excellent thermal conductivity and hardness and is considered an ideal reinforcement material. However, existing methods still face many challenges in achieving effective bonding between diamond and copper. Although there have been some attempts to prepare copper-based composites by mixing diamond particles with copper powder and using hot pressing and sintering, the preparation process of copper-based composites is complex, the cost is high, the interface fusion between diamond and copper is poor, and the interface bonding is not tight, resulting in poor thermal conductivity and high-temperature stability of semiconductor devices made of copper-based composites. Summary of the invention

[0005] In view of this, the purpose of the present invention is to provide a copper-based composite solder paste, a preparation method and application thereof, so as to solve the technical problems in the prior art such as poor interface fusion between diamond and copper, loose interface bonding, resulting in poor thermal conductivity and high-temperature stability of semiconductor devices made of copper-based composite materials.

[0006] In a first aspect, the present invention provides a copper-based composite solder paste, which comprises: nano-scale copper powder, micron-scale doped modified diamond powder, titanium powder, additives, solvents and resin.

[0007] Optionally, the mass ratio of the nano-scale copper powder, the micron-scale doped modified diamond powder and the titanium powder is 94-99: 0.5-5.0: 0.5-1.0, preferably 95-99: 0.5-5.0: 0.5-1.0.

[0008] Optionally, the micron-sized doped modified diamond powder is obtained by doping and modifying micron diamond, and the doping element is selected from at least one of boron, sulfur, nitrogen, phosphorus and magnesium.

[0009] Optionally, when the doping element is boron, the boron source used may be boron element, boron oxide, trimethyl borate or the like.

[0010] Optionally, when sulfur is used as the dopant, the sulfur source used includes but is not limited to: sulfur dioxide, hydrogen sulfide, dimethyl disulfide and other substances.

[0011] Optionally, when the doping element is nitrogen, the nitrogen source used includes but is not limited to: nitrogen, ammonia, ammonium chloride, melamine, and hexamethylenetetramine.

[0012] Optionally, when phosphorus is used as the doping element, the phosphorus source used includes but is not limited to: phosphine and other substances.

[0013] Optionally, when magnesium is used as the doping element, the magnesium source used includes but is not limited to: magnesium nitride, magnesium boride and other substances.

[0014] Optionally, the particle size of the nano-scale copper powder is ≤100 nm.

[0015] Optionally, the particle size of the titanium powder is 40-200 μm, preferably 50-200 μm.

[0016] Optionally, the solvent is selected from at least one of monohydric alcohol, polyhydric alcohol, polyethylene glycol and polyol ether.

[0017] In the present invention, examples of the monohydric alcohol include ethanol, terpineol and the like.

[0018] In the present invention, examples of the polyol include ethylene glycol, glycerol, diethylene glycol and the like.

[0019] In the present invention, examples of the polyol ether include ethylene glycol butyl ether, diethylene glycol hexyl ether, diethylene glycol octyl ether, tripropylene glycol butyl ether, and diethylene glycol dibutyl ether.

[0020] Optionally, the resin is selected from at least one of hydrogenated rosin, polymerized rosin, water-white rosin and terpene resin.

[0021] Optionally, the auxiliary agent includes a reducing agent and / or a surfactant.

[0022] Optionally, the reducing agent comprises ascorbic acid, ascorbate, or a combination of the two.

[0023] Optionally, the surfactant includes alkylphenol polyoxyethylene ether, alkenyl polyoxyethylene ether or a combination thereof.

[0024] Optionally, the particle size of the micron diamond is 10-50 μm, preferably 20-50 μm.

[0025] Optionally, the volume ratio of the auxiliary agent, the solvent and the resin is 10-20:80-90:5-10, preferably 15-20:80-90:5-10.

[0026] Optionally, the mass ratio of the nano-scale copper powder to the additive is in the range of 5:1-10:1, preferably 6:1-8:1.

[0027] In a second aspect, the present invention also provides a method for preparing the copper-based composite solder paste as described above, comprising the following steps:

[0028] S1. doping and modifying the micron diamond to obtain micron-sized doped modified diamond powder;

[0029] S2. Mixing the micron-sized doped modified diamond powder and titanium powder, grinding to obtain a mixed powder;

[0030] S3. Mixing additives, solvents and resins to obtain a mixed solution;

[0031] S4. Ultrasonic dispersion of the nano-scale copper powder and the mixed powder in the mixed liquid to obtain the copper-based composite solder paste.

[0032] Optionally, in the doping modification process of step S1, the temperature is 80-1100° C., preferably 90-1100° C.; the pressure is 8-15 KPa, preferably 9-15 KPa.

[0033] Optionally, in step S2, the grinding speed is 150-500 rpm, preferably 200-500 rpm; the grinding time is 4-10 h, preferably 4.5-10 h.

[0034] Optionally, in step S4, the temperature of the ultrasonic dispersion is ≤40°C, and the duration of the ultrasonic dispersion is 10-20 min, preferably 15-20 min.

[0035] In a third aspect, the present invention also provides a semiconductor device, comprising a metal substrate and a chip, wherein the metal substrate and the chip are connected by screen printing the copper-based composite solder paste as described above or the copper-based composite solder paste prepared according to the method as described above on the metal substrate, and then the chip is placed on the printed solder layer, followed by baking under vacuum conditions, and then connected together after hot pressing and sintering.

[0036] Optionally, the thickness of the metal substrate is 50-200 μm, preferably 60-200 μm.

[0037] Optionally, the baking temperature is 80-160° C., preferably 80-120° C.; the baking time is 5-30 min, preferably 5-15 min.

[0038] Optionally, the hot pressing sintering includes: heating to 220-350° C. at a heating rate of 5-15° C. / min, and keeping the temperature at 220-350° C. for 3-20 min.

[0039] Optionally, during the hot pressing sintering process, the pressure is 3-10 MPa, preferably 5-8 MPa.

[0040] As described above, the copper-based composite solder paste of the present invention, its preparation method and application have the following beneficial effects:

[0041] The copper-based composite solder paste of the present invention, by adding micron-level doped modified diamond powder (i.e., doping and modifying the micron diamond), can allow doping atoms such as boron, sulfur, nitrogen, phosphorus, and magnesium to penetrate into the crystal lattice of the micron diamond, which helps to improve the electrical conductivity. The improvement of the electrical conductivity helps to reduce the heating power of the solder layer, thereby improving the thermal conductivity and high-temperature stability of the semiconductor device.

[0042] In the preparation process of the copper-based composite solder paste of the present invention, by mixing and grinding the micron-sized doped modified diamond powder and the titanium powder, the micron-sized doped modified diamond powder and the titanium powder can be more fully contacted and mixed, and the bonding force between the diamond and the titanium powder is increased, so that a tighter interface bonding is formed in the subsequent sintering process, the tightness of the interface bonding is improved, the thermal conductivity performance is enhanced, and the thermal conductivity and high-temperature stability of the semiconductor device made of the solder paste are improved.

[0043] In the process of preparing the copper-based composite solder paste, the present invention controls the content of the micron-sized doped modified diamond powder in the mixed powder to a specific level, thereby maintaining the conductivity of the overall solder layer at the same order of magnitude as that of pure silver / copper metal, significantly improving the thermal conductivity of the semiconductor device (the thermal conductivity of diamond is 2200-2600 W·mk, and that of copper is 380-401 W·mk), reducing the difference in thermal expansion coefficient between the solder layer and the chip, and comprehensively improving the high-temperature stability of the semiconductor device.

[0044] In the preparation process of the copper-based composite solder paste, the present invention can improve the activation energy of the solder or reduce the copper oxide or cuprous oxide generated by copper and oxygen in the air during the sintering process to copper by adding an auxiliary agent (at least one of ascorbic acid, alkylphenol polyoxyethylene ether and alkenyl polyoxyethylene ether) into the mixed solution, thereby improving the thermal conductivity of the solder, improving the sintering quality in the subsequent sintering process, and further improving the thermal conductivity and high-temperature stability of the semiconductor device made of the solder paste.

[0045] The copper-based composite solder paste of the present invention can reduce the overall thermal expansion coefficient of the solder layer, thereby reducing the thermal stress between the chip and the solder layer during temperature changes, and further improving the thermal conductivity and high-temperature stability of the semiconductor device made of the solder paste.

[0046] The copper-based composite solder paste of the present invention can further improve the thermal conductivity of the solder layer while taking into account the electrical conductivity of the solder layer, improve the overall heat dissipation performance, and further improve the thermal conductivity and high-temperature stability of the semiconductor device.

[0047] The copper-based composite solder paste of the present invention has low cost and can reuse failed or scrapped diamond chips or electrode materials, etc., and has a wide source, thereby reducing costs. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] Figure 1 The present invention is a flow chart of a method for preparing a semiconductor device. DETAILED DESCRIPTION

[0049] The present invention is further described below through specific examples, but it should be pointed out that the specific material ratios, process conditions and results described in the embodiments of the present invention are only used to illustrate the present invention and cannot be used to limit the protection scope of the present invention. All equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

[0050] An embodiment of the present invention provides a copper-based composite solder paste, comprising: nano-scale copper powder with a particle size of ≤100 nm, micron-scale doped modified diamond powder, titanium powder with a particle size of 40-200 μm, additives, solvents and resin;

[0051] The mass ratio of nano-scale copper powder, micron-scale doped modified diamond powder and titanium powder is 94-99: 0.5-5.0: 0.5-1.0;

[0052] The mass ratio of nano copper powder to additive is in the range of 5:1-10:1;

[0053] The micron-sized doped modified diamond powder is prepared by doping and modifying micron diamond with a particle size of 10-50 μm, and the doping element is selected from at least one of boron, sulfur, nitrogen, phosphorus and magnesium;

[0054] The solvent is selected from at least one of monohydric alcohol, polyhydric alcohol, polyethylene glycol and polyol ether;

[0055] The resin is selected from at least one of hydrogenated rosin, polymerized rosin, water-white rosin and terpene resin;

[0056] The auxiliary agent includes a reducing agent and / or a surfactant. The reducing agent includes ascorbic acid, ascorbic acid salt or a combination thereof. The surfactant includes alkylphenol polyoxyethylene ether, alkenyl polyoxyethylene ether or a combination thereof.

[0057] The volume ratio of the additive, the solvent and the resin is 10-20:80-90:5-10.

[0058] The mass ratio of nano copper powder to additive is 94-99:10-20.

[0059] Another embodiment of the present invention also provides a method for preparing the copper-based composite solder paste as described above, comprising the following steps:

[0060] S1. doping and modifying the micron diamond to obtain micron-sized doped modified diamond powder;

[0061] S2. Mixing micron-sized doped modified diamond powder and titanium powder, grinding at a speed of 150-500 rpm for 4-10h to obtain a mixed powder;

[0062] S3. Mixing additives, solvents and resins to obtain a mixed solution;

[0063] S4. Ultrasonically disperse the micron-sized copper powder and the mixed powder in the mixed solution at a temperature of ≤40°C for 10-20 minutes to prepare a copper-based composite solder paste.

[0064] Another embodiment of the present invention also provides a semiconductor device, comprising a metal substrate with a thickness of 50-200 μm and a chip, wherein the metal substrate and the chip are connected by screen printing the copper-based composite solder paste as described above or the copper-based composite solder paste prepared according to the method as described above on the metal substrate with a thickness of 50-200 μm, and then the chip is placed on the printed solder layer, followed by baking under vacuum and 80-160° C. for 5-30 minutes, and then connected together after hot pressing and sintering.

[0065] The hot pressing sintering includes: heating to 220-350°C at a heating rate of 5-15°C / min, and keeping the temperature at 220-350°C for 3-20 minutes. During the hot pressing sintering process, the pressure is 3-10MPa.

[0066] The present invention is described in detail below by specific examples. It should also be understood that the following examples are only used to specifically illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not limited to the specific values ​​​​exemplified below.

[0067] Example 1

[0068] according to Figure 1 The process shown is used to produce semiconductor devices. The specific steps are as follows:

[0069] S1. Boron doping modification (i.e. high temperature and high pressure element doping, with gaseous borate triester as the boron source) of micron diamond with a particle size of 35 μm was performed at 1000°C and 8KPa to obtain micron-sized doped modified diamond powder;

[0070] S2. Mixing micron-sized doped modified diamond powder and titanium powder with a particle size of 100 μm in a mass ratio of 5:1, then putting them into a ball mill and grinding them at a speed of 300 rpm for 6 h under vacuum to obtain a mixed powder;

[0071] S3. Mixing ascorbic acid (i.e., active agent), ethylene glycol (i.e., organic carrier) and epoxy resin in a volume ratio of 12:80:8 under ultrasonic stirring to obtain a mixed solution;

[0072] S4. Add nano-copper powder with a particle size of 50 nm and mixed powder (the mass ratio of nano-copper powder to mixed powder is 94:6) into the mixed solution, and stir electromagnetically under ultrasonic environment at room temperature for 10 minutes to obtain a copper-based composite solder paste, wherein the mass ratio of nano-copper powder to ascorbic acid is 94:10;

[0073] S5. Print the copper-based composite solder paste on a copper substrate with a thickness of 70μm and a size of 10*10*1mm by screen printing, and paste the SiC SBD chip with a size of 4*4*0.18mm on it. After packaging, vacuum bake it for 15 minutes at a temperature of 120℃, then place it in a hot pressing device, vacuum and pressurize it to 5MPa, heat it to 300℃ at a heating rate of 10℃ / min, and keep it at 300℃ for 5 minutes, cool it to room temperature, and complete the interconnection of semiconductor devices.

[0074] Example 2

[0075] according to Figure 1 The process shown is used to produce semiconductor devices. The specific steps are as follows:

[0076] S1. Nitrogen doping modification (i.e. high temperature and high pressure element doping, ammonia as nitrogen source) of micron diamond with a particle size of 20 μm was performed at 950°C and 10 KPa to obtain micron-sized doped modified diamond powder;

[0077] S2. Mixing micron-sized doped modified diamond powder and titanium powder with a particle size of 150 μm in a mass ratio of 2:1, and then putting them into a ball mill and grinding them at a speed of 400 rpm for 5 h under vacuum to obtain a mixed powder;

[0078] S3. Mix ascorbic acid, ethylene glycol and epoxy resin in a volume ratio of 15:80:5 under ultrasonic stirring to obtain a mixed solution;

[0079] S4. Add nano-copper powder with a particle size of 30 nm and mixed powder (the mass ratio of nano-copper powder to mixed powder is 98.5:1.5) into the mixed solution, and stir electromagnetically under ultrasonic environment at room temperature for 15 minutes to obtain a copper-based composite solder paste, wherein the mass ratio of nano-copper powder to ascorbic acid is 100:20;

[0080] S5. Print the copper-based composite solder paste on a copper substrate with a thickness of 100μm and a size of 8*8mm by screen printing, and paste a SiC SBD chip with a size of 4*4*0.18mm on it. Evacuate the wafer after packaging, and bake it in a vacuum for 20 minutes at a temperature of 100°C. Then place it in a hot pressing device, evacuate it and pressurize it to 6MPa, heat it to 280°C at a heating rate of 12°C / min, keep it warm for 3 minutes, and cool it to room temperature to complete the interconnection of the semiconductor devices.

[0081] Comparative Example 1

[0082] The difference between this comparative example and Example 1 is that:

[0083] S2. Mix micron diamond (from the same source as in Example 1) and titanium powder with a particle size of 100 μm in a mass ratio of 5:1, then put into a ball mill and grind at a speed of 300 rpm for 6 hours under vacuum to obtain a mixed powder.

[0084] That is, the micron diamond was not doped and modified in this comparative example.

[0085] Comparative Example 2

[0086] The difference between this comparative example and Example 1 is that:

[0087] S4. Add nano-copper powder with a particle size of 30 nm and micron-sized doped modified diamond powder to the mixture, and stir the mixture under ultrasonic conditions at room temperature for 15 min. The mass ratio of nano-copper powder to micron-sized doped modified diamond powder is 98.5:1.5, and the mass ratio of nano-copper powder to ascorbic acid is 94:10.

[0088] That is, in this comparative example, titanium mixing and grinding of the micron diamond were not performed.

[0089] Comparative Example 3

[0090] The difference between this comparative example and Example 1 is that:

[0091] S2. Mix micron-sized doped modified diamond powder and titanium powder with a particle size of 100 μm in a mass ratio of 5:0.5, then put them into a ball mill and grind them at a speed of 300 rpm for 6 hours under vacuum to obtain a mixed powder.

[0092] That is, the amount of titanium powder used in this comparative example is too small.

[0093] Comparative Example 4

[0094] The difference between this comparative example and Example 1 is that:

[0095] S2. Mix micron-sized doped modified diamond powder and titanium powder with a particle size of 150 μm in a mass ratio of 2:1.5, then put them into a ball mill and grind them at a speed of 400 rpm for 5 hours under vacuum to obtain a mixed powder.

[0096] That is, the amount of titanium powder used in this comparative example is too much.

[0097] Comparative Example 5

[0098] The difference between this comparative example and Example 1 is that:

[0099] S3. Ethylene glycol and epoxy resin are mixed in a volume ratio of 98:8 under ultrasonic stirring to obtain a mixed solution.

[0100] That is, no auxiliary agent ascorbic acid was added to the mixed solution for comparison.

[0101] Comparative Example 6

[0102] The difference between this comparative example and Example 1 is that:

[0103] S4. Add nano-copper powder with a particle size of 50 nm and mixed powder (the mass ratio of nano-copper powder to mixed powder is 90:10) into the mixed solution, and stir it electromagnetically under ultrasonic environment at room temperature for 10 minutes to obtain a copper-based composite solder paste.

[0104] That is, the amount of mixed powder used is too much.

[0105] Performance Testing

[0106] The porosity, thermal resistance and thermal resistance attenuation rate of the solder layers of the semiconductor devices prepared in Examples 1-2 and Comparative Examples 1-6 after 20,000 cycles (6 min / cycle) of the power cycle test were tested, and the results are shown in Table 1;

[0107] The porosity detection method is as follows: according to the SEM image, the gray value of the image is counted by Image J software and the porosity is calculated by Image J software;

[0108] The thermal resistance detection method is: first calibrate the temperature sensitivity coefficient (i.e., K coefficient) of the chip through the K coefficient, and then calibrate the thermal resistance through the K coefficient. The parameters in the process of calibrating the temperature sensitivity coefficient (i.e., K coefficient) of the chip through the K coefficient are set as follows: the maximum current (data sheet rated value) is 40A, the small current is 100mA, the typical VF value is 1.5V (lower than 1.7V), the temperature rise range is 25℃ to 85℃, and every 20℃ is a point, and the K coefficient can be obtained;

[0109] The resistivity test method is as follows: Place the solder layer sample on the test platform at room temperature, ensure that the four probes are in good contact with the sample surface, pass a constant current, and measure the voltage drop according to the formula Calculate the resistivity of the welding layer (U is the voltage drop, S is the cross-sectional area of ​​the sample, I is the current, and L is the length of the sample);

[0110] The parameters in the process of calibrating thermal resistance by K coefficient are set as follows: import K coefficient, set transient heating current to 1 / 4 of rated current, set heating and cooling time to 150s, and then the thermal resistance can be obtained;

[0111] The thermal resistance decay rate detection method is: carry out 20,000 load power cycle tests under the conditions of power-on time of 2 minutes, cooling time of 4 minutes, and temperature difference of 80°C. After the test, detect the thermal resistance again according to the above method, and then calculate the thermal resistance decay rate according to the formula: thermal resistance decay rate = (thermal resistance before test - thermal resistance after test) / thermal resistance before test * 100%.

[0112] Table 1 Test results

[0113]

[0114] As shown in Table 1, compared with Comparative Example 1 (micron diamond is not doped and modified), the resistivity of the solder layer of Example 1 (micron diamond is doped and modified) is significantly reduced, and the thermal resistance attenuation rate is significantly reduced. This result shows that the present invention can make boron, sulfur, nitrogen, phosphorus, magnesium and other doping atoms penetrate into the lattice of micron diamond by adding micron-level doped and modified diamond powder (i.e. doping and modifying micron diamond), which helps to improve the electrical conductivity. The improvement of electrical conductivity helps to reduce the heating power of the solder layer, thereby improving the thermal conductivity of semiconductor devices (the thermal resistance in the prior art is usually 0.15-0.2K / W) and high temperature stability.

[0115] As shown in Table 1, compared with Comparative Example 2 (micron diamond was not mixed with titanium and ground), the resistivity of the welding layer of Example 1 (micron diamond was mixed with titanium and ground) was significantly reduced, and the thermal resistance attenuation rate was significantly reduced. This result shows that

[0116] In the preparation process of the copper-based composite solder paste of the present invention, by mixing and grinding the micron-sized doped modified diamond powder and the titanium powder, the micron-sized doped modified diamond powder and the titanium powder can be more fully contacted and mixed, and the bonding force between the diamond and the titanium powder is increased, so that a tighter interface bonding is formed in the subsequent sintering process, the tightness of the interface bonding is improved, the thermal conductivity performance is enhanced, and the thermal conductivity and high-temperature stability of the semiconductor device made of the solder paste are improved.

[0117] As shown in Table 1, compared with Comparative Example 3 (too little titanium powder in the mixed powder) and Comparative Example 4 (too much titanium powder in the mixed powder), the resistivity of the solder layer of Example 1 is significantly reduced, the thermal resistance of the solder layer is significantly reduced, and the thermal resistance attenuation rate is significantly reduced. The results show that in the process of preparing the copper-based composite solder paste, the present invention can significantly improve the thermal conductivity of the semiconductor device (the thermal conductivity of diamond is 2200-2600W·mk, and that of copper is 380-401W·mk) while maintaining the same order of electrical conductivity of the overall solder layer compared to pure silver / copper metal by controlling the content of micron-sized doped modified diamond powder in the mixed powder at a specific level, and reduce the difference in thermal expansion coefficient between the solder layer and the chip, thereby comprehensively improving the high temperature stability of the semiconductor device.

[0118] As shown in Table 1, compared with Comparative Example 5 (no auxiliary ascorbic acid was added to the mixed solution), the resistivity of the solder layer in Example 1 (additive ascorbic acid was added to the mixed solution) was significantly reduced, the thermal resistance of the solder layer was significantly reduced, and the thermal resistance attenuation rate was significantly reduced. This result shows that in the process of preparing the copper-based composite solder paste, the present invention can increase the activation energy of the solder or reduce the copper oxide or cuprous oxide generated by copper and oxygen in the air during the sintering process to copper by adding an auxiliary agent (at least one of ascorbic acid, alkylphenol polyoxyethylene ether and alkenyl polyoxyethylene ether) to the mixed solution, thereby improving the thermal conductivity of the solder, improving the sintering quality in the subsequent sintering process, and thus improving the thermal conductivity and high temperature stability of the semiconductor device made of the solder paste.

[0119] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.

Claims

1. A copper-based composite solder paste, characterized in that: The copper-based composite solder paste comprises: nano-scale copper powder, micron-scale doped modified diamond powder, titanium powder, additives, solvent and resin, wherein the micron-scale doped modified diamond powder is prepared by doping and modifying micron diamond, and the doping element is selected from at least one of boron, sulfur, nitrogen, phosphorus and magnesium; The mass ratio of the nano-scale copper powder, the micron-scale doped modified diamond powder and the titanium powder is 94-99: 0.5-5.0: 0.5-1.0; The volume ratio of the auxiliary agent, solvent and resin is 10-20:80-90:5-10; The mass ratio of the nano-scale copper powder to the additive is in the range of 5:1-10:1; The particle size of the nano-scale copper powder is ≤100nm; The particle size of the titanium powder is 40-200 μm; The solvent is selected from at least one of monohydric alcohol, polyhydric alcohol, polyethylene glycol and polyol ether; The resin is selected from at least one of hydrogenated rosin, polymerized rosin, water-white rosin and terpene resin; The auxiliary agent includes a reducing agent, and the reducing agent includes ascorbic acid, ascorbic acid salt or a combination thereof.

2. The copper-based composite solder paste according to claim 1, characterized in that: The auxiliary agent also includes a surfactant.

3. The copper-based composite solder paste according to claim 2, characterized in that: The surfactant includes alkylphenol polyoxyethylene ether, alkenyl polyoxyethylene ether or a combination of the two.

4. The method for preparing the copper-based composite solder paste according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1. doping and modifying the micron diamond to obtain micron-sized doped modified diamond powder; S2. Mixing the micron-sized doped modified diamond powder and titanium powder, grinding to obtain a mixed powder; S3. Mixing additives, solvents and resins to obtain a mixed solution; S4. Ultrasonically disperse the micron-sized copper powder and the mixed powder in the mixed liquid to obtain the copper-based composite solder paste.

5. The method for preparing the copper-based composite solder paste according to claim 4, characterized in that: In step S2, the grinding speed is 150-500 rpm, and the grinding time is 4-10 hours; And / or, in step S4, the temperature of the ultrasonic dispersion is ≤40°C, and the duration of the ultrasonic dispersion is 10-20 min.

6. A semiconductor device comprising a metal substrate and a chip, characterized in that: The metal substrate and the chip are connected by screen printing the copper-based composite solder paste according to any one of claims 1 to 3 or the copper-based composite solder paste prepared by the method according to claim 4 or 5 on the metal substrate, and then placing the chip on the printed solder layer, followed by baking under vacuum conditions, and then connecting them together after hot pressing and sintering.

7. The method for producing a semiconductor device according to claim 6, characterized in that: The thickness of the metal substrate is 50-200 μm; And / or, the baking temperature is 80-160° C., and the baking time is 5-30 min; And / or, the hot pressing sintering comprises: heating to 220-350°C at a heating rate of 5-15°C / min, and keeping at 220-350°C for 3-20min; And / or, during the hot pressing sintering process, the pressure is 3-10 MPa.

Citation Information

Patent Citations

  • Metallic particle paste, cured product using same and semiconductor device

    CN104425055A

  • Preparation method of compact combined composite material for electronic packaging

    CN111029309A

  • Copper particle soldering paste and preparation method and sintering method thereof

    CN112351598A

  • Pastes for thermal, electrical and mechanical bonding

    US10308856B1